2019
DOI: 10.3390/molecules24224132
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants of Natural Plant Origins: From Sources to Food Industry Applications

Abstract: In recent years, great interest has been focused on using natural antioxidants in food products, due to studies indicating possible adverse effects that may be related to the consumption of synthetic antioxidants. A variety of plant materials are known to be natural sources of antioxidants, such as herbs, spices, seeds, fruits and vegetables. The interest in these natural components is not only due to their biological value, but also to their economic impact, as most of them may be extracted from food by-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
463
0
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 767 publications
(601 citation statements)
references
References 185 publications
1
463
0
26
Order By: Relevance
“…The antioxidants (natural or synthetic) can act through different mechanisms in the organism, such as: (i) direct neutralization of free radicals; (ii) expression of molecules from the host antioxidant defense systems; (iii) inhibition of oxidant enzymes (leading to reduction of free radicals' generation/propagation) [10][11][12][13]. These compounds can also be used in the food industry to maintain the physical-chemical quality of fruits, meat, and other foods [14][15][16]. Due to the side effects of synthetic antioxidants, those from natural sources are preferred; this context leads to a constant search for plant-derived compounds with this property [4,[10][11][12][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidants (natural or synthetic) can act through different mechanisms in the organism, such as: (i) direct neutralization of free radicals; (ii) expression of molecules from the host antioxidant defense systems; (iii) inhibition of oxidant enzymes (leading to reduction of free radicals' generation/propagation) [10][11][12][13]. These compounds can also be used in the food industry to maintain the physical-chemical quality of fruits, meat, and other foods [14][15][16]. Due to the side effects of synthetic antioxidants, those from natural sources are preferred; this context leads to a constant search for plant-derived compounds with this property [4,[10][11][12][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SFE is carried out in the absence of light and oxygen, which reduces the degradation of the compounds. Thus, the use of SFE-CO 2 is an efficient alternative process to conventional solvent extraction methods, especially for extracting lipophilic plant materials [3].…”
Section: Green Technique: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Furthermore, in order to maintain the acceptable colour, some additives as nitrite or colourants could also be added to meat. However, several studies indicated a relationship between synthetic additives intake and some health issues [3] leading to increased consumer demands for more natural products. This fact limits the industry in their use of synthetic additives in foods, leaving manufacturers with few options [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations